Analysis of the Effectiveness of Implementing Fingerprint Attendance on the Discipline of ASN and NON ASN Employees in the Pondokgede District Education Service Unit - Rochayati Febriarhamadini (MultiTech Publisher, 2023)
The development of the times is increasingly advanced so that it also has an impact on technological progress. The system that was previously manual has now become electronic, such as the implementation of fingerprint attendance. This research aims to determine the effectiveness of using Attendan cefingerprints regarding the discipline of ASN and non-ASN employees in the Pondokgede District Education Service Unit under the Bekasi City Education Service. This research is descriptive qualitative research, the data source utilizes primary data and data collection through interviews with informants. The interview results were analyzed using the listening method and note-taking method. Results of research on the effectiveness of using Attendan cefingerprints The discipline of ASN and non-ASN employees in the Pondokgede District Education Service Unit is measured through indicators measuring program effectiveness including target achievement, adaptability, job satisfaction and responsibility. Based ontarget achievement, where the implementation of fingerprint attendance is a government target that has been well realized and when implemented in the Pondokgede District Education Service Unit had a quite good impact on improving employee discipline and performance. Second, the ability to adapt, at the beginning of implementation there were problems, one of the factors was that employees had not adapted to the on-time arrival and departure times according to the rules given by the Mayor of Bekasi. Third, job satisfaction, when fingerprint attendance was implemented, increased, which was supported by no TPP (Additional Employee Income) deductions for ASN and no salary/income deductions for Non-ASN if they attended and worked optimally. Fourth responsibility, since the implementation of fingerprint attendance, ASN and non-ASN employees in the Pondogede District Education Service Unit are quite good because they have their respective responsibilities both in terms of attendance and reporting the results of their performance.